Comparative Analysis Of Usability Value On Online Shop Fashion Websites Using The System Usability Scale (SUS) - Marpaung, Gaby Novitaria Dwi Andika; Astiti, Sarah; Fernandez, Sandhy (Journal of INISTA, 2023)
The results of the We Are Social survey in April 2021, Indonesia is a country that has the highest percentage of e-commerce usage in the world. The increasing use of e-commerce in Indonesia and the most sought-after e-commerce products in the fashion sector make online fashion shops potentially good in Indonesia. The development of e-commerce engaged in fashion apart from having a mobile application, there is also a website that can be accessed without having to download it on the device used. The quality of an e-commerce website affects the number of users who choose to shop online from an e-commerce website. This research aims to find out whether there are differences in the usability value of websites in the field of online shop fashion contained in the top brand award in the retail category. The websites are Zalora.co.id, Berrybenka.com, Fashiontoday. co, and Cottonink.co.id. Knowing the usability level of the website uses the System Usability Scale (SUS) method. The four websites have different average SUS scores but for the grading scale, the four websites are in grade D, the adjective scale is in the OK category, acceptable is at the marginal level, and NPS is in the detractor category.